Share it - don't own it: Space sharing as a smart solution for cities and regions? - Hirschler, Petra; Zech, Sibylla (My University, 2014)
"Have space you don't fully use? Offer for people to rent it. Make some money." (uniiverse 2013) With this slogan, the Platform uniiverse advertises their internet service to share private spaces - from couch, rooms and apartments, offices, storage, gymnasiums, parking lots to all kinds of rooms. After times of seemingly limitless growth and endless consumption, the scarcity of resources is obvious and requires resource friendly and saving planning concepts. Concepts like Smart City and Smart Region have a strong focus on technological solutions and newly built structures. How to handle the existing settlements and housing stock? Are only newly built neighbourhoods smart cities? In any case, there is need for smart spatial concepts and smart approaches for existing structures. One possibility of smart development in the existing structures is the sharing of space and infrastructure. In the field of mobility different sharing models are common. Starting with the shared space (an urban design approach which seeks to minimise demarcations between vehicle traffic and pedestrians) und to the traditional public transport. Car sharing is also offered by private sector as the project Sharoo successfully shows (sharoo AG 2013). With exchange platforms like Napster the idea of shared economy became mainstream. But the real benefit of collaborative consumption and sharing turns out to be social. In an era of individualism, the peer-to-peer sharing "involves the re-emergence of community," says Rachel Botsman (2010) and is therefore very important in bottom-up planning process, because people learn to trust each other (ibid). Seoul adopted the "Sharing City, Seoul" strategy in 2012 and has been promoting and supporting the shared economy my and their start- ups specifically, but also focuses on the sharing and more intense use of infrastructure. Did this idea already spread? Are there other cities and regions following this exciting way? Which smart sharing models can contribute to spatial planning and development?
Keywords: Stadtplanung; Stadtentwicklung; Flächennutzung; Straßenraum; Innovation; Beispielsammlung; Shared space; Entwicklungsmodell; Flächensparen; Ressourceneinsparung; Gemeinschaftsnutzung; Nutzungsvielfalt